Is Social Responsibility Present in the Agenda of the National Educational Policy Documentations? View from a DIALLS Projection - Duobliene, Lilija; Kaire, Sandra; Zaleskiene, Irena (Acta Paedagogica Vilnensia, 2020)
The article familiarizes the reader with the main goals and implementation structures of the DIALLS (Dialogue and Argumentation for Cultural Literacy Learning in Schools) three-year project (2018–2021), supported by EU Research and Innovation program HORIZON 2020. The project is coordinated by Cambridge University in partnership with 9 EU universities. In Lithuania project activities are implemented by the Institute of Educational Sciences at Vilnius University. The theoretical concept of Social Responsibility in the context of Cultural Literacy and Educating for an Active Citizenship is analysed in the theoretical part of the article. Some empirical data on addressing the concept of Social responsibility in the National Educational Policy documentation is presented and discussed from the view of DIALLS projection. Finally, some concluding points on addressing the concepts of Social responsibility, participation, cooperation and citizenship in the national educational policy documentation are drawn up.
Keywords: Social responsibility; Citizenship; Participation; Cooperation; Educational Policy documentation